Enhancing academic engagement: Growth mindset and academic buoyancy in emerging adulthood - Fatimah, Siti; Suharsono, Yudi (Jurnal Ilmiah Psikologi Terapan, 2025)
Academic engagement is key for students' academic success, life satisfaction, and overall student well-being. Emerging adult students often face various pressures that significantly influence their AE. This study aims to explore the mediating role of AB in the influence of a GM on AE among emerging adults. The study engaged with 314 students selected through convenience sampling. The instruments used were the GM Inventory, AB Scale, and Ultra-Short Utrecht Work Engagement Scale for data collection. The data were analyzed through Structural Equation Modeling using AMOS software. The findings demonstrated a positive and significant correlation between a GM and both AB and engagement. Notably, AB was found to significantly influence AE and played a substantial mediating role in the relationship between a GM and AE. The implications of these findings indicate that institutions should implement support programs aimed to enhancing AB and fostering a GM among students, thereby improving their AE, considering the complexity of interactions among these factors.